(untitled) (International relations and international law Journal, 2019)
Abstract. This article analyzes the specifics of marriage complicated by a foreign element. In accordance with the national legislation of the Republic of Kazakhstan, even stateless persons and foreign citizens who have confirmed their belonging to a foreign state are equally subject to protection in matters of family and marriage with citizens of the Republic of Kazakhstan. The application of the family law of the Republic of Kazakhstan in the presence of foreign elements is impossible without reference and appeal to the norms of international treaties, especially in the context of p. 3st.4 of the Constitution stating that the “...International treaties ratified by the Republic have priority over its laws”. It follows that in case of collision of provisions of the national legislation of the Republic of Kazakhstan and norms of the international Treaty ratified by Kazakhstan regulating the same question of marriage and family relations, the norm of the international Treaty will have priority action. Currently, the Republic of Kazakhstan has ratified, through the adoption of the relevant law, a significant number of international treaties in the field under study. As for marriages between foreign citizens or stateless persons and citizens of the Republic of Kazakhstan, concluded outside Kazakhstan, but in compliance with the current legislation of the state in whose territory they were concluded, are recognized as valid in the Republic of Kazakhstan. At the same time, conceptually important is the fact of compliance with the requirements of the relevant norms of the CMF RK. Key words: Marriage, family, foreign element, registration, conflicts.